PENERAPAN AJARAN TRI PARARTHA DALAM PENDIDIKAN KARAKTER AGAMA HINDU BAGI SISYA PASRAMAN DHARMAGITA, BLIMBING, KECAMATAN KARANGNONGKO, KABUPATEN KLATEN - Devi Ardika Putri; Dewi Ayu Wisnu Wardani; Shinta Tyas Pratisthita (Jawa Dwipa, 2025)
This study aims to examine the application of the Tri Parartha teachings in Hindu character education for students at the Dharmagita Pasraman (Islamic school) in Blimbing Village, Karangnongko District, Klaten Regency. The Tri Parartha teachings, which encompass Asih (compassion), Punia (punia), and Bhakti (blessing), are viewed as the foundation of moral values ​​in shaping students' character, who are noble, responsible, and able to socialize harmoniously. This study employed a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The informants included pasraman administrators, teachers, students, and parents. Data analysis was conducted using the Miles and Huberman interactive model, comprising data reduction, presentation, and conclusion drawing. The results indicate that the application of the Tri Parartha teachings at the Dharmagita Pasraman plays a significant role in shaping students' character, as reflected in increased compassion, social awareness, responsibility, and consistency in religious practices such as Tri Sandya (tri-sandying) and ngayah (ngayah). The implementation of the Tri Parartha teachings is integrated with the Pancasila Student Profile (P5) through learning activities, mutual cooperation, dialogue, and hands-on practice. Supporting factors include the availability of infrastructure and environmental support for the pasraman, while inhibiting factors include the limited space of the pasraman building and suboptimal teacher participation. Overall, this study confirms that character education based on the Tri Parartha teachings has a positive impact on the personality and behavioral development of pasraman students.